Sedimentary processes at ice sheet grounding-zone wedges: comparing planform morphology from the western Ross Sea (Antarctica) to internal stratigraphy from outcrops of the Puget Lowlands (Washington State, U.S.A.) - Demet, Brian Patrick (2016)
The current understanding of sedimentary processes that produce ice sheet grounding-zone wedges (GZWs) is limited because most observations derive from marine geophysical techniques, including seismic and multibeam instruments, as well as isolated cores from these sediment deposits. Collectively, these data may provide measurements of large-scale morphology and internal stratigraphy, but are typically of inadequate resolution to identify the range of sediment transport processes that produce GZWs. Herein, newly acquired high-resolution seismic and multibeam data from the western Ross Sea, Antarctica, are used to document GZW planform geometries, which are compared to interpreted GZW outcrops exposed on Whidbey Island, Washington (U.S.A.), in order to link planform morphology and sedimentary transport processes at ice grounding lines to internal stratigraphy. These efforts document that GZWs possess self-similar planform geometries, and that the size range of GZWs may be adjusted to include deposits that are less than ten meters thick and hundreds of meters in length. For the Whidbey Island outcrop deposits, prograding successions are bounded by glacial unconformities, whereby the upper unconformity indicates glacial over-ridding during episodes of grounding line stability. The dominant mode of GZW construction is determined to be sediment mass movement in the form of debris flows, and delivery of deformation till by ice to the grounding line by ice. The role of meltwater discharge in terms of sediment dispersal and accumulation is found to vary, and both channelized flows and sediment-laden plumes are interpreted. Rhythmic beds of silt and sand provide evidence of tidal pumping. Collectively, these observations indicate a punctuated style of ice sheet retreat, with stability lending to the growth of GZW, during overall grounding line back-stepping during deglaciation. Based on evidence from the Puget Lowlands, including radiocarbon ages, the timescale of stability between retreat events is on the order of ...